2005
DOI: 10.1111/j.1365-313x.2005.02356.x
|View full text |Cite
|
Sign up to set email alerts
|

The atypical resistance gene, RPW8, recruits components of basal defence for powdery mildew resistance in Arabidopsis

Abstract: SummaryGenetic studies have identified a number of components of signal transduction pathways leading to plant disease resistance and the accompanying hypersensitive response (HR) following detection of pathogens by plant resistance (R) genes. In Arabidopsis, the majority of R proteins so far characterized belong to a plant superfamily that have a central nucleotide-binding site and C-terminal leucine-rich-repeats (NB-LRRs). Another much less prevalent class comprises RPW8.1 and RPW8.2, two related proteins th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
189
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(203 citation statements)
references
References 73 publications
9
189
1
Order By: Relevance
“…In addition, edr1 mutants display enhanced growth inhibition and spontaneous cell death in response to drought (Tang et al, 2005b), and enhanced cell death mediated by the RPW8 powdery mildew resistance gene (Xiao et al, 2005). All of these phenotypes, except for ethyleneinduced senescence, can be suppressed by mutations in the SA signaling pathway (sid2, npr1, pad4, and eds1; Frye et al, 2001;Tang et al, 2005b;Xiao et al, 2005). However, edr1 mutant plants do not show constitutive expression of SA-inducible genes when grown under optimal conditions (Frye and Innes, 1998), thus it has been unclear why loss of EDR1 function leads to these various phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, edr1 mutants display enhanced growth inhibition and spontaneous cell death in response to drought (Tang et al, 2005b), and enhanced cell death mediated by the RPW8 powdery mildew resistance gene (Xiao et al, 2005). All of these phenotypes, except for ethyleneinduced senescence, can be suppressed by mutations in the SA signaling pathway (sid2, npr1, pad4, and eds1; Frye et al, 2001;Tang et al, 2005b;Xiao et al, 2005). However, edr1 mutant plants do not show constitutive expression of SA-inducible genes when grown under optimal conditions (Frye and Innes, 1998), thus it has been unclear why loss of EDR1 function leads to these various phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The newly obtained accessions were tested with E. cichoracearum UCSC1 three times using the method previously described (Xiao et al 2003(Xiao et al , 2005. Among the 51 accessions surveyed, there was a range of disease reaction (DR) phenotypes from very resistant to very susceptible.…”
Section: Methodsmentioning
confidence: 99%
“…How powdery mildew pathogens cause disease and how RPW8 detects the pathogens and induces resistance in A. thaliana are not clear. However, RPW8 appears to activate defense through a conserved signaling pathway that is also utilized by a subset of NBS-LRR R genes (Xiao et al 2003(Xiao et al , 2005. Our previous evolutionary analysis indicated that the origin of the RPW8 locus is relatively young, probably after the separation of Arabidopsis from the Brassica lineages and that RPW8.1 and RPW8.2 evolved from an HR3-like progenitor gene by duplication and functional diversification (Xiao et al 2004).…”
mentioning
confidence: 99%
“…G. cichoracearum UCSC1 causes powdery mildew disease on some Brassicaceae and Cucurbitaceae species (Adam et al, 1999;Braun et al, 2002), and can establish either incompatible or compatible interactions with different Arabidopsis accessions (Adam and Somerville, 1996). Resistance against different Golovinomyces species is mediated by monogenic traits (Xiao et al, 1997(Xiao et al, , 2001Adam et al, 1999) such as that conferred by the RPW8 locus, which encodes a small novel protein conferring resistance against a wide range of powdery mildews (Xiao et al, 2001(Xiao et al, , 2005. In contrast, the conditions promoting compatibility have been less well characterized.…”
mentioning
confidence: 99%